KEMAJUAN DAN PROSPEK: DIPLOMASI MARITIM PRESIDEN JOKOWI DAN POROS MARITIM GLOBAL - Simatupang, Helga Yohana (Dinamika Global : Jurnal Ilmu Hubungan Internasional, 2023)
When President Joko “Jokowi” Widodo first came into power in 2014, he introduced his vision and commitment of transforming Indonesia into a global maritime fulcrum (GMF), highlighting the notion as his first grand strategy of his administration’s foreign policy. President Jokowi promoted the concept in multiple international meetings abroad, in which his foreign minister, Retno Marsudi, echoed the same ideas to various international dignitaries. President Jokowi’s administration even took it further by codifying the vision in 2017 through a Presidential Regulation on National Sea Policy. However, when President Jokowi took oath for a second term in 2019, it seems there have been less enthusiasm from himself and his newly sworn in administration regarding the grand strategy. This is shown with even the words surrounding the grand strategy have not been mentioned by the president or his ministers. Even though President Jokowi and his administration have not been blatant regarding the global maritime vision, the concept is still very much relevant and viable for such a vast archipelagic nation like Indonesia. The first term of Jokowi’s presidency has shown efforts of implementation of the GMF concept, but various limitations in economic, security, and foreign policy aspects have halted the progress. Maritime diplomacy is still a very important concern that President Jokowi must push before leaving office and will be an important legacy for his successor to build upon in the next administration. Despite that economic transformation and recovery have been the priority of President Jokowi’s second term administration, it withholds the potential of Indonesia if a wider spectrum of maritime strategy is not brought forward. Indonesia holds the capacity to become a global maritime power and it is unjust to the nation if the country does not hold the steering wheel of maritime influence in the region. The GMF may have not been the strongest starting point, but neither should the concept be dismissed completely. It could always be built on with a more comprehensive and systematic strategy in order to reach the same means. Though the current state of the GMF lies more on the side of rhetoric, the materialization of the idea should not be a halted relay at the current administration. Bridging the progress of the GMF with the prospects that it holds in the future should be brought upon in the transition of power when Indonesia elects its next president in 2024. Keywords: Global Maritime Fulcrum, Maritime Diplomacy, Foreign Policy, Jokowi, Indonesia